2009
DOI: 10.1186/2047-783x-14-8-345
|View full text |Cite
|
Sign up to set email alerts
|

The time of diagnosis impacts surgical management but not the outcome of patients with gallbladder Carcinoma

Abstract: Background Only 50% of gallbladder cancers (GBC) are recognized before operation and the remaining tumors are diagnosed during surgery or afterwards by the pathologist. These situations may demand substantial modifications of the proceeding during surgery as well as the need for reoperation in some cases. Therefore, the time of diagnosis may strongly influence the surgical management of GBC and the prognosis of the patients. Methods Records and follow-up of 152 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…The site of care is a notable factor in survival outcomes, and case volume improves patient outcomes in ACCs. Given that at least 30% of patients with GBC are diagnosed preoperatively, selecting the site of care is an important decision and these data should be an informative resource to benefit this population 3,4 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The site of care is a notable factor in survival outcomes, and case volume improves patient outcomes in ACCs. Given that at least 30% of patients with GBC are diagnosed preoperatively, selecting the site of care is an important decision and these data should be an informative resource to benefit this population 3,4 …”
Section: Discussionmentioning
confidence: 99%
“…Sixty to seventy percent of GBC cases are discovered incidentally during surgery or on postoperative histopathology. Thirty to forty percent of patients are suspected preoperatively to have GBC and referral is possible 3,4 …”
Section: Introductionmentioning
confidence: 99%
“…The incidence of incidental GBC in gall bladder removed laparoscopically is 0.2-3.3% 9,10 . Approximately 3,700 new cases of GBC are documented annually in USA, 50% of which are diagnosed incidentally either intra-operatively (29%) or after laparoscopic cholecystectomy (21%) [11][12][13] .…”
Section: Discussionmentioning
confidence: 99%
“…Löhe et al [ 10 ] reported that only 50% of gallbladder cancers are recognized preoperatively. There could be several reasons for the difficulty recognizing cancers preoperatively.…”
Section: Introductionmentioning
confidence: 99%